2018
DOI: 10.29333/ejmste/94228
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Pre-service Teachers’ Social Media Usage in Informal Settings and Technological Pedagogical Content Knowledge

Abstract: Social media are increasingly adopted in university administration, teaching, and learning. For pre-service teachers, although there is growing evidence suggesting the effectiveness of educational technology courses in enhancing their technological pedagogical content knowledge (TPACK), relatively little is known about whether and how this knowledge is associated with social media usage (SMU) in informal settings. In this study, the relationships between SMU in informal settings and TPACK among pre-service tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
(45 reference statements)
2
15
0
1
Order By: Relevance
“…Although previous research shows, TPACK correlates with the use of technology level (Kazu & Erten 2014), educational internet use (Sahin, Celik, Akturk, & Aydin, 2013), attitude towards computer (Baturay, Gökçearslan, & Sahin, 2017), attitude towards web-based instruction (Kavanoz, Yüksel, & Ozcan, 2015) and SMU in informal setting or leisure activities (Lau, 2018), no research connect it with SMU in an academic setting or school activities. Lau (2018) suggested that extended research of SMU in an academic setting and specific domain should be identified as an area for future research, especially in the context of Science Education. Previous studies (Kaya, Kaya, & Emre, 2013;Lin, Tsai, Chai, & Lee, 2013;Pamuk, Ergun, Cakir, Yilmaz, & Ayas, 2015;Schmidt et al 2009) supported that TPACK could be domainspecific.…”
Section: Gaps In the Literaturementioning
confidence: 95%
See 4 more Smart Citations
“…Although previous research shows, TPACK correlates with the use of technology level (Kazu & Erten 2014), educational internet use (Sahin, Celik, Akturk, & Aydin, 2013), attitude towards computer (Baturay, Gökçearslan, & Sahin, 2017), attitude towards web-based instruction (Kavanoz, Yüksel, & Ozcan, 2015) and SMU in informal setting or leisure activities (Lau, 2018), no research connect it with SMU in an academic setting or school activities. Lau (2018) suggested that extended research of SMU in an academic setting and specific domain should be identified as an area for future research, especially in the context of Science Education. Previous studies (Kaya, Kaya, & Emre, 2013;Lin, Tsai, Chai, & Lee, 2013;Pamuk, Ergun, Cakir, Yilmaz, & Ayas, 2015;Schmidt et al 2009) supported that TPACK could be domainspecific.…”
Section: Gaps In the Literaturementioning
confidence: 95%
“…Social media is also integrated into Moodle to support distance learning (Buus, 2012). Lau (2018) investigates the correlation between SMU in informal settings (outside of classroom context), including for Media Sharing, Internet Searching, and Video Gaming with TPACK level of pre-service teachers with Path Analysis. He found that Media Sharing is a useful predictor of Technological Knowledge (TK) and Knowledge of Teaching with Technology (KTT).…”
Section: Social Media Usage (Smu) and Tpackmentioning
confidence: 99%
See 3 more Smart Citations